HOLOPROSENCEPHALY: FETAl, NEUROLOGICAL AND CLINICAL ASPECTS, PRENATAL DIAGNOSTICS, CASES FROM PRACTICE - T.V. Avramenko; A.A. Shevchenko (Bukovynian State Medical University, 2019)
The work is dedicated to rare and severe congenital malformation of the central nervous system - holoprosencephaly - through disorder of the differentiation of the telencephalon into two hemispheres, with modern presentation of the principles of prenatal diagnostics, embryological, neurological and clinical aspects of this pathology. Two cases of holoprosencephaly in combination with agenesis of the corpus callosum and hypoplasia of the cerebellar vermis (case number 1) and hypoplasia of the corpus callosum and spina bifida in the lumbosacral spine (case number 2) have been described. It was grounded the necessity of the use of modern neuroimaging techniques - magnetic resonance imaging for optimization of the prenatal diagnostics of congenital anomalies of the central nervous system and timely correction of obstetric tactics in order to reduce perinatal and infant mortality and childhood disability